Database Modeling Automation from Natural Language Requirements - Menezes, Júlia O. K.; Campelo, Claudio E. C. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais do XL Simpósio Brasileiro de Bancos de Dados, 2025)
This paper proposes an approach to support relational database modeling through the automatic generation of Entity-Relationship (ER) diagrams from natural language requirements, leveraging Large Language Models (LLMs) combined with prompt engineering. The method extracts entities, relationships, and attributes from textual descriptions to produce visual ER diagrams. The evaluation was conducted in two phases: first, by testing different LLMs based on structured criteria; and second, by validating the results with students familiar with database modeling. The results indicate that, while challenges remain in handling cardinalities and nullable constraints, the generated diagrams generally align well with the original requirements. These findings reinforce the potential of LLMs to enhance conceptual database modeling.